NON-VERBAL COMMUNICATION IN TEACHING PHYSICAL EDUCATION: AN ESSENTIAL PEDAGOGICAL TOOL - Otamirzayev Otabek Murodulla O'g'li (International Scientific and Current Research Conferences, 2023)
This essay emphasizes the significance of non-verbal communication in the context of teaching physical education (PE). Non-verbal communication, encompassing gestures, facial expressions, and body language, proves essential in conveying instructions effectively, motivating students, fostering a positive learning environment, and managing the classroom. Through non-verbal cues, teachers can enhance understanding, stimulate engagement, and create a conducive atmosphere for learning, ultimately optimizing the educational experience in physical education.